The Dynamics of Inheritance in Various Modern Muslim Countries - M. Taufiq Agiel; Adji Pratama Putra; Ahmad Mustofa; Alma Depa Yanti; Muhammad Hilmi Ajjahidi (Al Mashaadir : Jurnal Ilmu Syariah, 2023)
Islamic inheritance law is an important expression of Islamic family law which is a half of the knowledge possessed by humans as emphasized by the Prophet Muhammad Saw. Islamic inheritance laws basically apply to Muslims anywhere in the world. Islamic inheritance law stipulates that children can be replace their father's position, both sons and daughters. The purpose of this research is to find out how Islamic inheritance law is implemented in several Muslim countries in the world. This research uses a library research types with a normative juridical approach. The research was conducted by collecting data as the main source such as books, journal articles and other data which were analyzed by Islamic law. The research is described normatively clearly according to the existing data. The results of this study indicate that the law of inheritance in Islam states that a child who can replace his father's position is a son and daughter from the male lineage whose father has died before the heir. Meanwhile, sons and daughters from the female lineage have no right at all to replace their mother's position to obtain property from their grandfather (heir). Besides that, the culture of a Muslim country and the social life of the people in that country have an influence on the inheritance law in that country.